PENGARUH KOMPENSASI DAN KOMPETENSI TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA KEPADA KINERJA PEGAWAI DINAS KETAHANAN PANGAN DAN PETERNAKAN PROVINSI SUMATERA SELATAN - Fatmawati, Enab; AE, Edizal; Noviantoro, Djatmiko (JEMBATAN (Jurnal Ekonomi, Manajemen, Bisnis, Auditing, dan Akuntansi), 2025)
This study was conducted to determine the effect of compensation and competence on job satisfaction and its impact on employee performance at the Food Security and Livestock Service of South Sumatra Province, using quantitative methods, Likert scale calculations, Validity tests and reliability tests using SEM based on variants with Smart PLS software. The results of this study indicate that there is a positive and significant influence between compensation on job satisfaction, Competence has a positive and significant effect on job satisfaction, there is an influence of job satisfaction on performance, there is an indirect positive and significant influence of compensation on performance mediated by job satisfaction and an indirect positive influence of competence on performance mediated by job satisfaction. This means that the relationship between compensation, competence and job satisfaction together with employee performance shows a strong and positive correlation which provides an understanding that employee performance can be explained or influenced by compensation (X1), competence (X2) which is mediated through Job Satisfaction (Y).